Securing on methods for conduct of tests for patentabiliti of millet varieties (Panicum miliaceum L.) - О. І. Рудник (Plant Varieties Studying and Protection)
То argue and the paper presents of fundamental positions method for test new varieties millet of distinctness, uniformity and stability to development by results of Institute of Agriculture of UAAS.